2017
DOI: 10.3390/su9081323
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Footprint Analysis Based on Changing Food Consumption in a Poorly Developed Area of China

Abstract: Abstract:The per capita ecological footprint (EF) is a useful tool to compare consumption with nature's ability to support this consumption. Guyuan is an economically impoverished region in China, where EF provides important insights into whether human consumption can be sustained by the local per capita biological capacity (BC), which represents the environment's ability to support resource use. We estimated the EF of food consumption using local equivalence and yield factors, and compared EF in 1998 and 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
(68 reference statements)
0
13
0
1
Order By: Relevance
“…Shi et al 2009, Zhang and, and then consequence to the changes in livestock grazing and income (e.g. Alam 2013, Li et al 2015, Zhen and Du 2017. The external (natural) factors of ecosystem states (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al 2009, Zhang and, and then consequence to the changes in livestock grazing and income (e.g. Alam 2013, Li et al 2015, Zhen and Du 2017. The external (natural) factors of ecosystem states (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al 2013 and socio-economic conditions (e.g. Brown et al 2013, Zhen et al 2014, Koenig et al 2015, Zhen and Du 2017, in order to better understand the coupled human-earth system (e.g. Folke et al 2002, Chen et al 2015, Lee et al 2015, Monier et al 2017, Tong et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…To maintain multiple ecosystem services, it is necessary to seek an optimal spatial allocation of human activities that will minimize their negative environmental impacts. Growing recognition of the need for such analyses has led to the incorporation of ecosystem analysis as a mandatory component of ecosystem management in many countries (Pan et al, 2013;Zhen and Du, 2017). In addition, there is also a critical need for new studies that reveal the simultaneous changes in provision of multiple services so that managers can better understand the tradeoffs involved in the delivery of ecosystem services and look for solutions and synergies (Bennett et al, 2009).…”
Section: Background and Problem Statementmentioning
confidence: 99%
“…Fan, et al [22] took non-renewable resources and water resources into consideration, presented a modified ecological footprint accounting model to appraise the environmental impact of an industrial park-Hefei economic and technological development area. Zhen and Du [23] estimated the ecological footprint of food consumption in Guyuan City of Ningxia Hui Autonomous region by using ecological footprint models. Dai, et al [24] modified the EF model by using component analysis and considering the main features of a historic district, then they constructed the ecological footprint model of historic districts in two dimensions: residents and tourists.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that the per capita EF and ecological deficit of Guyuan significantly decreased after the project. Zhen and Du [23] suggested that the Grain for Green program increased the biological capacity (BC) of forest and grassland, but it also decreased the BC of cultivated land. In addition, some literatures has investigated the new agricultural animal husbandry projects (such as the "hog-biogas-fish" system) [37], national nature reserves [38], the ecological footprint of food consumption of residents [39,40].…”
Section: Literature Reviewmentioning
confidence: 99%